2003
DOI: 10.1097/00007632-200304010-00015
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Statistical analysis showed that a successful surgical outcome was dependent on both the structural changes in the thoracic curve and the patient's maturity. The thoracolumbar/lumbar-thoracic (TL/L:T) Cobb ratio in combination with the degree of the thoracic curve on lateral bending was the best predictor among the structural indexes. Of 44 patients with a TL/L:T Cobb ratio of 1.25 or greater and/or a thoracic curve, which bent out to 20 degrees or less, 42 had a satisfactory result. The best predictor among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Selective fusion has gained popularity over decades. 2,3,57 Although both anterior and posterior selective TL/L fusion turned out to be effective treatments for AIS with structural TL/L curve and compensatory thoracic curve, 3,8–15 studies have figured out that the anterior method may result in a higher incidence of kyphosis, pseudarthrosis, and loss of correction. 16 Posterior selective TL/L fusion has many advantages like better curve correction, less loss of correction overtime, less loss of blood, and shorter hospital stays over anterior approach, 12 and it has been widely accepted by spine surgeons in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Selective fusion has gained popularity over decades. 2,3,57 Although both anterior and posterior selective TL/L fusion turned out to be effective treatments for AIS with structural TL/L curve and compensatory thoracic curve, 3,8–15 studies have figured out that the anterior method may result in a higher incidence of kyphosis, pseudarthrosis, and loss of correction. 16 Posterior selective TL/L fusion has many advantages like better curve correction, less loss of correction overtime, less loss of blood, and shorter hospital stays over anterior approach, 12 and it has been widely accepted by spine surgeons in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, 36 % of our patients who underwent selective thoracolumbar/lumbar anterior spinal fusion sustained adding-on and 29 % showed coronal decompensation. Sanders et al [ 23 ] looked at 49 patients with AIS who underwent selective thoracolumbar/lumbar instrumented spinal fusion and tried to identify factors to predict a satisfactory outcome postoperatively. A TL/L:MT Cobb ratio >1.25 in combination with a MT curve that corrects to <20° on side-bending was the best structural predictor for a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Sanders et al [13] found significantly better major and minor curvature correction rates without any neurological problem and improved pulmonary function with posterior pedicle screw instrumentation as compared with segmental hook instrumentation. Betz et al [14] reported that coronal correction and balance were equal in both anterior and posterior groups.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior segmental pedicle screw fixation without anterior release had resulted in satisfactory deformity correction in severe scoliosis without significant loss of curvature correction. In this series, a single posterior procedure obviated the need for the anterior release and eliminated complications related to anterior surgery [13]. …”
Section: Discussionmentioning
confidence: 99%